Implementasi Pemberian Tablet Fe Pada Remaja Putri Di Wilayah Puskesmas Tapin Utara Kabupaten Tapin - Hartati, Endang; Dona, Sismeri; Irawan, Angga (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Anemia is a health problem that is currently often found in the world. In Tapin Regency, South Kalimantan, the coverage of giving blood-added tablets to adolescent girls in 2021 was 24.14%. Meanwhile, the incidence of anemia in 2022 is 29.3%. The purpose of the study was to determine the implementation of Fe tablets for adolescent girls at the North Tapin Health Center. Type of descriptive research with quantitative research methods. Respondents 58 people, total sampling technique. The data collection method uses questionnaires and secondary data with report recording. Data analysis using univariate analysis. Based on the results of research on the input component is 100% good, from human resources already exist but for infrastructure facilities such as counseling media, nutrition implementation cards are still lacking, in the process component 100% it has run well but on taking Fe tablets with assistance and clouding and recording needs to be improved, The output component is 100% good, female students want to take Fe tablets but some female students experience obstacles such as nausea making them reluctant to drink, the impact component of giving 100% Fe tablets is good for learning concentration.